Papillary Carcinoma in a Patient with a Thyroid Nodule: Role of Ultrasonography and its Diagnostic Accuracy - Muhammad Noor Khan, Ijaz Ahmad Sahibzada Fakhre Alam, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: While it can be difficult to categorize thyroid lesions, employing ultrasound may enable correct diagnosis, classification, and therapy of thyroid nodules, particularly papillary carcinoma of the thyroid, and assist save unneeded biopsy. Objective: Taking histopathology as the gold standard, assessing the diagnostic precision of ultrasound in the identification of papillary cancer in thyroid nodule patients. Study design: Cross sectional study Study Settings: Department of ENT & Surgery, Jinnah Teaching Hospital, Peshawar Study Duration: This study was conducted from 1st August 2021 till 30th June 2022. Materials and Methods: Patients of both gender who sought assessment for a thyroid nodule were included. On ultrasonography, papillary carcinoma was detected. The gold standard for diagnosing cancers, histology, was used to confirm papillary carcinoma. Using a 2×2 table, diagnostic accuracy was assessed in terms of sensitivity, specificity, PPV, and NPV. Results: Overall 241 participants recruited. The patients were between the ages of 18 and 75. The patients' mean age was 57.80 + 9.245 years. The ratio of men to women was 1.2:1. The ultrasound's sensitivity, specificity, PPV, NPV, and diagnostic accuracy for the diagnosis of papillary thyroid cancer were, respectively, 85.1%, 97.5%, 88.8%, 96.5%, and 95.1%. Conclusion: With clinically significant diagnostic accuracy for the early diagnosis of thyroid papillary carcinoma, ultrasound is a cost-effective, non-invasive diagnostic method that may lessen the need for invasive diagnostic methods like thyroid biopsy. Keywords: Papillary Carcinoma of Thyroid, Ultrasound, Diagnostic Accuracy